1994
DOI: 10.1002/ajpa.1330930402
|View full text |Cite
|
Sign up to set email alerts
|

Further analysis of mandibular molar crown and cusp areas in Pliocene and early Pleistocene hominids

Abstract: Crown and cusp areas of mandibular molars were measured and analyzed on a sample of 249 specimens attributed to Australopithecus afarensis, A. africanus, A. (Paranthropus) robustus, A. (P.) boisei, and early Homo. In addition to intertaxon comparisons, we compared data that had been collected independently by two of the authors using methods that differ slightly in technique of measurement. Interobserver differences were evaluated by the t-test of paired comparisons, method error statistic, percent differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 39 publications
4
76
1
Order By: Relevance
“…Magnitude of error, as expressed by the method error statistic, is broadly comparable to that of traditional mesiodistal and buccolingual crown dimensions (e.g., Mizoguchi, 1977) or of projected area measurements of the molar crown (Suwa et al, 1994). It can be concluded that the repeatability accuracy of our method of measuring enamel thickness is sufficient for actual use.…”
Section: Resultssupporting
confidence: 54%
“…Magnitude of error, as expressed by the method error statistic, is broadly comparable to that of traditional mesiodistal and buccolingual crown dimensions (e.g., Mizoguchi, 1977) or of projected area measurements of the molar crown (Suwa et al, 1994). It can be concluded that the repeatability accuracy of our method of measuring enamel thickness is sufficient for actual use.…”
Section: Resultssupporting
confidence: 54%
“…tion of these is available in Suwa (1988, one-way ANOVA tests on taxon means, while 1990, in press) and Suwa et al (1994) and principal components and canonical variate is not repeated here.…”
Section: Methodsmentioning
confidence: 99%
“…A 53 noted that ''the individual cups involved in the talonid expansion are not always the same,'' with the hypoconid and the entoconid contributing more to talonid expansion in P. boisei and P. robustus, respectively. This suggests that the derived dental morphology in the two Paranthropus taxa may not have the same developmental basis.…”
Section: How Many Species?mentioning
confidence: 99%